Efficacy of chlorhexidine gluconate in reducing surgical site infections after emergency caesarean delivery: a randomized controlled trial - Gabbeta, Spandana; Sethi, Pruthwiraj; Jena, Saubhagya Kumar; Mahapatra, Ashoka; Selvan, Advika; Baji, Dheeraj (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Caesarean delivery (CD) is a major, life-saving surgical procedure, with emergency CDs posing a greater risk for Surgical Site Infections (SSIs) due to compromised preoperative preparation. SSIs are common hospital-acquired infections, significantly increasing morbidity and healthcare costs. Preoperative skin antisepsis is critical for SSI prevention, with recent evidence suggesting Chlorhexidine Gluconate (CG) may be superior to Povidone Iodine (PI). This study was done to compare the efficacy of CG versus PI for skin antisepsis before emergency CD at AIIMS Bhubaneswar. Methods: This was a parallel-arm, single-blinded, randomized controlled trial. Four hundred and fifty women undergoing emergency CD were randomized to receive either CG or PI for preoperative skin antisepsis. Participants were observed for 30 days duration postoperatively to assess the primary outcome of SSI development. Secondary outcomes included hospital stay, re-suturing, readmission, and pyrexia. Statistical analysis involved Chi-square, Fisher’s exact, and Wilcoxon-Mann-Whitney U tests. Results: SSI occurred in 1.8% (4/225) of the CG group and 6.2% (14/225) of the PI group, a statistically significant difference (p = 0.016). Most SSIs were superficial, with no significant difference in type between groups. No significant differences were found in secondary outcomes. Higher BMI was significantly associated with SSI in both groups, and prolonged surgery duration in the CG group. Conclusions: CG significantly reduced SSI incidence compared to PI in emergency CD. This supports CG’s superior antiseptic properties and suggests its use can effectively mitigate SSI risk in this high-risk population.